Evaluating the Impact of Personalized Medicine on Cancer Treatment Outcomes (Journal of Medical & Health Sciences Review, 2025)
Background:Personalized medicine has revolutionized cancer treatment by tailoring therapies to individual genetic and molecular profiles, enabling more targeted and effective interventions. Advances in genomic technologies, such as Next-Generation Sequencing (NGS), and biomarker analyses have allowed for precise identification of actionable mutations and personalized treatment strategies. However, understanding the clinical and economic implications of these approaches remains a priority to optimize their application in cancer care.Objective:This study aims to evaluate the clinical and economic impact of personalized medicine on cancer treatment outcomes, focusing on progression-free survival (PFS), overall survival (OS), quality of life, and cost-effectiveness. By comparing patients receiving personalized treatments with those undergoing standard care, the study seeks to assess the benefits and challenges associated with precision oncology.Methods:A retrospective cohort study was conducted at tertiary cancer centers, including patients diagnosed with breast, lung, and pancreatic cancer who underwent personalized medicine interventions. Genomic and molecular profiling was performed using NGS and biomarker analyses (e.g., PD-L1, EGFR, BRCA mutations). Outcomes such as PFS and OS were analyzed using Kaplan-Meier survival analysis and Cox proportional hazards models. Cost-effectiveness was evaluated through incremental cost-effectiveness ratio (ICER) calculations. Data sources included electronic health records (EHRs), cancer registries, and genomic databases such as The Cancer Genome Atlas (TCGA).Results:Patients receiving personalized medicine interventions demonstrated significantly improved PFS and OS compared to those on standard therapies (PFS: median 12.4 vs. 8.3 months; OS: median 24.6 vs. 18.7 months, p < 0.05). Biomarker-driven therapies exhibited the highest efficacy, particularly among patients with actionable mutations such as EGFR and BRCA. Cost-effectiveness analysis revealed that personalized medicine, while initially more expensive, resulted in better quality-adjusted life years (QALYs), making it economically viable in the long term.Conclusion:The findings underscore the transformative potential of personalized medicine in enhancing cancer treatment outcomes, with notable improvements in survival and quality of life. However, high costs and accessibility challenges must be addressed to ensure broader adoption. Future research should focus on scaling these interventions and exploring their utility across diverse populations and cancer types.